Measurement report: Rocket-borne measurements of large ions in the mesosphere and lower thermosphere – detection of meteor smoke particles - J. Stude; J. Stude; H. Aufmhoff; H. Schlager; M. Rapp; M. Rapp; C. Baumann; F. Arnold; B. Strelnikov (Atmospheric Chemistry and Physics)
We present mass spectroscopic in situ data from rocket flights of two improved ion mass spectrometers in the mesosphere and lower thermosphere region. The instruments were optimized to detect large ions with a mass-to-charge ratio (m/z<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="23pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="91270dba487782af7360c80516416e4b"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-25-383-2025-ie00001.svg" width="23pt" height="14pt" src="acp-25-383-2025-ie00001.png"/></svg:svg>, mass) of up to m/z<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="23pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="63c7f3946b001d4e8415de9c4a1834dd"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-25-383-2025-ie00002.svg" width="23pt" height="14pt" src="acp-25-383-2025-ie00002.png"/></svg:svg> 2000 and 20 000 respectively, for analysis of meteor smoke particles. The flights were performed in the framework of the polar mesospheric winter echo (PMWE) campaigns, initiated and coordinated by the Leibniz Institute of Atmospheric Physics (IAP), to investigate polar mesospheric winter radar echoes in Andøya (Norway) in 2018 and 2021. Both flights were successful and allowed the mass number and chemical composition of charged meteor smoke particles to be investigated. We found a complex and diverse composition of positively and negatively charged molecules and particles within our mass range in a region that is notoriously difficult to get mass spectroscopic data from. While at altitudes below 85 km we observed negatively charged particles of up to several thousands of atomic mass units, above this altitude we found possible building blocks of these large particles that form right after their ablation from the parent meteorite material. In the first flight we detected no positively charged particles above m/z<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="23pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="d797e7418bb082ad5eec13189d6e5a75"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-25-383-2025-ie00003.svg" width="23pt" height="14pt" src="acp-25-383-2025-ie00003.png"/></svg:svg> 100 and a difficult-to-interpret signal for negatively charged particles beyond our mass range of m/z<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="23pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="55e7511b997f0b1e1b80fcef0834494e"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-25-383-2025-ie00004.svg" width="23pt" height="14pt" src="acp-25-383-2025-ie00004.png"/></svg:svg> 2000. In the second flight, however, we detected positively charged particles between around m/z<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="23pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="46f32566b65c77f385ccc58250dc589d"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-25-383-2025-ie00005.svg" width="23pt" height="14pt" src="acp-25-383-2025-ie00005.png"/></svg:svg> 180 and 350 and a number of different negatively charged particles up to m/z<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="23pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="ab5624c790cbaa3f5350f350107808ad"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-25-383-2025-ie00006.svg" width="23pt" height="14pt" src="acp-25-383-2025-ie00006.png"/></svg:svg> 5500. Due to the very large mass range of m/z<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="23pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="82359dc0e2bbce7906032009eb1b5089"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-25-383-2025-ie00007.svg" width="23pt" height="14pt" src="acp-25-383-2025-ie00007.png"/></svg:svg> 20 000 used in the second flight and the subsequent lower mass resolution, unambiguous mass identification is not possible. A particular interesting pattern was found at 80.8 km of a compound that seems to double its mass around m/z<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="23pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="d93d3cda2a0fb8602765a5ab31f8bec1"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-25-383-2025-ie00008.svg" width="23pt" height="14pt" src="acp-25-383-2025-ie00008.png"/></svg:svg> 225, 450, 900 and 1800.